2008
DOI: 10.1088/0953-8984/20/32/325224
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ferroelectric properties of [C3N2H5]5[Bi2Br11]

Abstract: A ferroelectric crystal [C3N2H5]5[Bi2Br11] has been synthesized and structurally characterized at 170 and 100 K. The crystal structure consists of discrete corner-sharing bioctahedra [Bi2Br11]5− and highly disordered imidazolium cations. The room temperature crystal structure has been determined as monoclinic, space group, P 21/n with: a = 9.257(2) Å, b = 15.157(3) Å, c = 13.865(3) Å and β = 97.73(3)°. The crystal undergoes two solid–solid phase transitions: at 355 K of first-order and at 155 K of second-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…The I-I distance of 3.5410(1) Å is significantly shorter then the sum of the van der Waals radii (4.12 Å), and the angle h 1 that is equal to 177.6u gives almost a linear configuration. The I … N distance is equal to 3.505(5) Å in N(1)-H(1) … I(1) bond and donor-to-acceptor angle equals 170 (7)u. The basic hydrogen and halogen bonded pattern is a ten membered ring.…”
Section: Structure Discussionmentioning
confidence: 99%
“…The I-I distance of 3.5410(1) Å is significantly shorter then the sum of the van der Waals radii (4.12 Å), and the angle h 1 that is equal to 177.6u gives almost a linear configuration. The I … N distance is equal to 3.505(5) Å in N(1)-H(1) … I(1) bond and donor-to-acceptor angle equals 170 (7)u. The basic hydrogen and halogen bonded pattern is a ten membered ring.…”
Section: Structure Discussionmentioning
confidence: 99%
“…It is suggested that the lone pair (5s 2 -Sb(III) and 6s 2 -Bi(III)) has a key role in the collective properties of these ferroelectric materials [11]. Recently, we have synthesized three novel ferroelectrics from the haloantimonate(III) and halobismuthate(III) family of compounds crystallizing with the chemical composition R 5 M 2 X 11 , where R is the imidazolium cation [19,20]. It is rather intriguing that all known compounds (imidazolium, pyridinium, or methylammonium cations) with this composition have been found to exhibit ferroelectric properties, whereas formally very similar compounds crystallizing with H 2 O molecules, ðR 5 M 2 X 11 Á 2H 2 OÞ, do not reveal any ferroelectric properties [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is known, however, that in the case of 2D ferroelectrics, characterized by the R 3 M 2 X 9 composition, their cations, such as monomethyl-, dimethyl-or trimethylammonium [12][13][14], are rather small. On the other hand, in the R 5 M 2 X 11 compounds the polar properties are found in either the small alkylammonium cations (methylammonium) or the aromatic ones (pyridinium and imidazolium) [15][16][17][18]. The ferroelectricity of these subgroups of crystals is due to the reorientational motion of the organic cations possessing a permanent dipole moment.…”
Section: Introductionmentioning
confidence: 99%